2020
DOI: 10.1111/fare.12468
|View full text |Cite
|
Sign up to set email alerts
|

Relational Upheaval During Refugee Resettlement: Service Provider Perspectives

Abstract: Objective We seek to provide insight on intimate relationships and service provider response for refugees during the resettlement transition in the United States. Background Refugees resettling in the United States face numerous stressful transitions that could affect their relationships with intimate partners. Thus, refugees may be at risk for increased relationship upheaval, yet typical options for support are limited by migration and a potentially unsupportive political climate. Frontline service providers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, some forced migrant fathers do take up domestic roles, relieving the burden of the mother and find themselves having closer relationships with their children (Matthiesen, 2019; Stewart et al , 2015). Conflict in relationships due to new gender norms are found to be accepted at different rates depending on the outlook of the partner, which may either strengthen or weaken relationships (Tlapek et al , 2020). All parents may experience role expansion, but single mothers may find themselves additionally taking on the traditional gendered role of fathers being the provider and the disciplinarian (Amadala, 2012).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…However, some forced migrant fathers do take up domestic roles, relieving the burden of the mother and find themselves having closer relationships with their children (Matthiesen, 2019; Stewart et al , 2015). Conflict in relationships due to new gender norms are found to be accepted at different rates depending on the outlook of the partner, which may either strengthen or weaken relationships (Tlapek et al , 2020). All parents may experience role expansion, but single mothers may find themselves additionally taking on the traditional gendered role of fathers being the provider and the disciplinarian (Amadala, 2012).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…In another study, a change in women's attitudes was reported to depend on their education level, English proficiency, personal experience of IPDV, years of living in the host country, connecting with the host society, and pursuing education in the new home (Afrouz et al 2021b). Tlapek, S. M. and colleagues also reported that refugee women in their host countries encounter new gender roles that can increase daily relational confrontations; refugee women may stand up to their partners, ask for shared decision-making, and no longer tolerate inadequate pre-resettlement gender norms (Tlapek et al 2020).…”
Section: Thematic Analysismentioning
confidence: 99%
“…In the new environment, women have less trust and take their marital challenges from the family. Most women do not share their IPDV or relationship challenges with providers, only with trusted family or friends (Tlapek et al 2020). Abdel Meguid et al also mentioned that women prefer family members as the first source of help-seeking, followed by friends and then the Imam, and lastly to get help from formal authorities and shelters.…”
Section: Stakeholders' Attitudes And/or Behaviors Toward Ipdvmentioning
confidence: 99%
See 1 more Smart Citation